Analisis Character Building (Nilai Karakter Mandiri dan Integritas Siswa) pada Pembelajaran Jarak Jauh - Indri Caesari Yanti; Armida S (Jurnal Ecogen, 2022)
This study aims to explain how the value of independent character and integrity of class XI students of SMA Negeri 6 Tanjung Jabung Barat in distance learning. Which is seen from the observations of all class XI subject teachers, totaling 25 subject teachers. This type of research is descriptive research with a survey approach that uses primary data as research data. Obtained from a questionnaire filled out by all class XI subject teachers and in-depth interviews with economics teachers who teach the subject of national income. Sampling by purposive sampling. The analysis technique used is descriptive analysis and TCR (Respondent Achievement Level). The findings of this study indicate that distance learning for class XI students of SMA Negeri 6 Tanjung Jabung Barat has given birth to attitudes that reflect the values of independent character and integrity. Therefore, these character values can be realized in the form, namely (1) significant school rules and regulations for the implementation of character education (2) optimizing the role of school organizations that support student character education (3) teachers using models and methods that more varied and innovative in the learning process.Keywords : character building, independent and integrity character, online learning